2023
DOI: 10.1007/s11250-023-03680-7
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of genetic parameters for semen traits in Egyptian buffalo bulls

Abstract: This study was conducted to characterize semen traits (ejaculate volume (VOL), mass motility (MM), sperm livability (LS), percentage of abnormal sperms (AS), and sperm concentration (CONC)) of Egyptian buffalo bulls and evaluate the importance of some nongenetic factors (year (YC) and season (SC) of semen collection and age of bull genetically and environmentally at collection (ABC)) affecting the investigated traits. A total of 7761 normal semen ejaculates were collected from 26 bulls from 2009 to 2019. Singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 25 publications
4
3
0
Order By: Relevance
“…These results are consistent with Tables 4 and 5 , where MM, LS, and CONC are strongly associated with PC1, and VOL and AS are more closely associated with PC2. These results are consistent with those of Salem et al ( 2023 ), where the results of genetic correlation is highest between the traits abnormality and the same is true for the traits Motility, live and Concentrate. The prior correlation coefficients between the various PC characteristics represented the complex interactions between these seminal traits as well as the genetic basis of the quantitative traits, which were controlled by a number of genes, each of which contributed differently to each trait.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…These results are consistent with Tables 4 and 5 , where MM, LS, and CONC are strongly associated with PC1, and VOL and AS are more closely associated with PC2. These results are consistent with those of Salem et al ( 2023 ), where the results of genetic correlation is highest between the traits abnormality and the same is true for the traits Motility, live and Concentrate. The prior correlation coefficients between the various PC characteristics represented the complex interactions between these seminal traits as well as the genetic basis of the quantitative traits, which were controlled by a number of genes, each of which contributed differently to each trait.…”
Section: Resultssupporting
confidence: 93%
“…0.08 ± 0.07 for VOL and 0.04 ± 0.04 for AS) and low genetic correlations between traits (e.g. 0.17 ± 0.74 between VOL and MM and 0.22 ± 0.72 between VOL and LS) as shown in Salem et al ( 2023 ).…”
Section: Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…The overall mean values for VOL, MM, LS, AS, and CONC exhibited a degree of similarity to those previously reported by Salem et al (2023) [21] based on a subset of the current data from the IMTC herd. The authors reported that the measured values for VOL, MM, LS, AS, and CONC were 3.89 mL, 62.37%, 60.64%, 3.94%, and 0.67 × 10 9 spermatozoa/mL, respectively.…”
Section: Discussionsupporting
confidence: 82%